Influence of travel demands and match load on recovery following postmatch travel in national-team footballers - Clements, E.; Ehrmann, F.; Clark, A.; Jones, M.; McCall, A.; Duffield, R. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This study investigated the relationship between travel demands and match loads on perceptual recovery, fatigue, and sleep following postmatch travel in national football teams. In addition, the influence of travel demands and the time between match kickoff and travel departure on postmatch recovery was examined.